Market Orientation A Study On Hotels Of Penang - Mendiratta, Sumit (2003)

(untitled)
Industri perhotelan merupakan suatu industri yang berkembang pesat, ianya memainkan peranan yang penting kepada ekonomi setiap negara. Perkembangan yang ,- pesat telah meningkatkan cabaran di antara pesaing. Dalam lingkungan rangkakerj a perancangan strategik, pengurusan harus membuat keputusan pemasaran yang kritikal. Tujuan kajian ini adalah untuk memberi pemahaman kepada orientasi pasaran secara amnya, dan membantu pengurus dalam penentuan penyebab yang menentukan orientasi pasaran ini dalam industri perhotelan. Kajian ini telah dilaksanakan dengan mencadangkan suatu rangkakerja teoritikal berasaskan model Kohli dan Jaworski (1993) untuk mengkaji perhubungan di antara penyebab orientasi pasaran dan akibat orientasi pasaran dalam industri perhotelan di Pulau Pinang. Hotel industry is one of the important industries that play a major role in economy of every country. The rapid expansion increases the challenges among competitors. For one to succeed in the business, the business must be market oriented and customer driven. Within a strategic-planning framework, managers must make critical marketing decisions. The purpose of this study was to contribute to the general understanding of market orientation and to assist managers in determining antecedents that contributes to market orientation as well as to understand the consequences of applying market orientation in the hotel industry. This study was conducted, by proposing a theoretical framework made from Kohli and Jaworski Model, to investigate the relationship between antecedents of market orientation as well the consequences of market orientation in hotel industry of Penang. A questionnaire was generated from the Kohli and Jaworski (1993) research.